MicroRNA-124 inhibits cancer cell growth through PTB1/PKM1/PKM2 feedback cascade in colorectal cancer. Issue 1 (10th July 2015) - Taniguchi, Kohei; Sugito, Nobuhiko; Kumazaki, Minami; Shinohara, Haruka; Yamada, Nami; Nakagawa, Yoshihito; Ito, Yuko; Otsuki, Yoshinori; Uno, Bunji; Uchiyama, Kazuhisa; Akao, Yukihiro
Highlights: The expression levels of miR-124 were decreased in clinical colorectal cancer (CRC) and adenoma (CRA) patients' samples. MiR-124 induced apoptosis and/or autophagic survival in human colon cancer cells. MiR-124 targeted PTB1 to modulate the Warburg effect through the switching of PKM isoform expression from PKM2 to PKM1. Abstract: Altered levels and functions of microRNAs (miRs) have been associated with carcinogenesis. In this study, we investigated the role of miR-124 in colorectal adenoma (CRA) and cancer (CRC). The expression levels of miR-124 were decreased in CRA (81.8%) and CRC (57.6%) in 55 clinical samples. The ectopic expression of miR-124 induced apoptosis and autophagy in colon cancer cells. Also, miR-124 targeted polypyrimidine tract-binding protein 1 ( PTB1 ), which is a splicer of pyruvate kinase muscles 1 and 2 ( PKM1 and PKM2 ) and induced the switching of PKM isoform expression from PKM2 to PKM1. Also, siR-PTB1 induced drastic apoptosis in colon cancer cells. Furthermore, we found that the ectopic expression of miR-124 enhanced oxidative stress and the miR-124/PTB1/PKM1/PKM2 axis constituted a feedback cascade. Finally, we showed that intratumor injection of miR-124 and siR-PTB1 induced a tumor-suppressive effect in xenografted mice. The axis was established by both in vitro and in vivo experiments to function in human colorectal cancer cells. These findings suggest that miR-124 acts as a tumor-suppressor and a modulator of energy metabolism through a PTB1/PKM1/PKM2 feedback cascade in human colorectal tumor cells.